(untitled) (Malay Literature, 2018)
One of the most important aspects of Islamic teachings is nature (fitrah). Muslims are obliged to believe in nature as something that has existed since its creation. Man is believed to have the potential of becoming Muslim, so he is obligated to devote himself to Allah, the Creator. Some people are not born Muslim but later enter into Islam, such as Norjannah MA, who was born a non-muslim but later became a muallaf, a Muslim revert. As a Muslim revert, she most likely goes through the process of understanding her new religion. The purpose of this paper is to examine the return to the fitrah-the original or natural state-as experienced by Norjannah MA herself, and how it is addressed in her work titled Kumpulan Puisi Yang Menyala (2017). This study uses the theory of fitrah criticism, which is based on three principles namely the pattern, system and aesthetics of fitrah, or the natural state. The results of this study show that the love and belief of God (akidah) which burns in her heart becomes a dominant pattern of nature. Seeking God’s love is not easy and the natural state (fitrah) shows that anger is often a strong impediment to Norjannah. In comparison to the natural aesthetic, the natural pattern and system discussed are not expressed poetically. Arabic terms are widely used, and their presence interferes with the author’s expression, as well as the reader’s appreciation of the text. Keywords: fitrah, fitrah critism, Norjannah M.A., Kumpulan puisi yang menyala